THE LEGACY OF SPICE ROUTE: THE ROLE OF PANGLIMA LAOT IN MARITIME SECURITY IN THE MODERN ACEH - Mu’aqaffi, Gaffar (Jurnal Masyarakat dan Budaya, 2022)
Panglima Laot is a cultural institution that has existed for a long time in Aceh. Starting in the 17th century, Panglima Laot consistently made an essential contribution to the coastal communities of Aceh, especially in preserving the marine environment by implementing and enforcing Adat Laot. While most research only discussed Panglima Laot's contribution to Aceh’s marine environment with its unique customary law, this research aspires to explore the role of Panglima Laot in the context of maritime security in Aceh. By utilising the maritime security matrix from Bueger, this study found that Panglima Laot contributed to realising four critical elements of maritime security: human security, marine environment, economic development, and national security. The contribution was obtained from the effective cooperation carried out by maritime security stakeholders in Aceh with Panglima Laot. These maritime security stakeholders are Aceh Regional Police, the Department of Maritime Affairs and Fisheries of Aceh Province, and the Indonesian Navy.